Reading Books and Reading Minds: Differential Effects of Wonder and The Crossover on Empathy and Theory of Mind - Martha S. Guarisco; Celine Brooks; Louise M. Freeman (University of Oklahoma Libraries, 2017)
We tested sixth graders for empathy and theory of mind before and after an academic unit on either Wonder or The Crossover. Wonder was associated with improved perspective-taking; students who read The Crossover increased in concern for others. Faux pas detection increased in both genders with Wonder, and in girls with The Crossover. Students who read The Crossover in print showed improved understanding of facial expressions, while students who used iPads declined. Young adult fiction is associated with improved social cognitive skills, but effects depend on gender and reading format, as well as on the choice of individual book.